Type I Interferons: Key Players in Normal Skin and Select Cutaneous Malignancies - Aimen Ismail; Nabiha Yusuf (Dermatology Research and Practice)
Interferons (IFNs) are a family of naturally existing glycoproteins known for their antiviral activity and their ability to influence the behavior of normal and transformed cell types. Type I Interferons include IFN-α and IFN-β. Currently, IFN-α has numerous approved antitumor applications, including malignant melanoma, in which IFN-α has been shown to increase relapse free survival. Moreover, IFN-α has been successfully used in the intralesional treatment of cutaneous squamous cell carcinoma (SCC) and basal cell carcinoma (BCC). In spite of these promising clinical results; however, there exists a paucity of knowledge on the precise anti-tumor action of IFN-α/β at the cellular and molecular levels in cutaneous malignancies such as SCC, BCC, and melanoma. This review summarizes current knowledge on the extent to which Type I IFN influences proliferation, apoptosis, angiogenesis, and immune function in normal skin, cutaneous SCC, BCC, and melanoma.